Pendidikan Karakter Tokoh Dewi Angreni dalam Naskah Panji Wulung Wayang Gedhog - Futya Rakhmani; Yusi Nurcahya Dewi; Agatia Mega Rianda (Perkumpulan Dosen Muslim Indonesia - Sulawesi Selatan, 2025)
This study aims to examine the character education of Dewi Angreni in the Panji Wulung Wayang Gedhog script, focusing on the value of integrity and mutual cooperation. The research method used is descriptive qualitative approach with literary sociology approach. Data were obtained from Panji Wulung manuscripts and analyzed using hermeneutic techniques. The results showed that Dewi Angreni is a protagonist who has a strong character in the form of loyalty, obedience to her husband, and concern for others. The value of integrity is reflected in her loyalty until the end of her life, while the value of mutual cooperation is seen in her concern for others and respect for others. This study confirms that Dewi Angreni can be used as a role model inlearning local wisdom-based character education